Variation of match statistics and football teams’ match performance in the group stage of the EUFA Champions league from 2010 to 2017 (Kinesiology, 2019)
The aim of this study was to identify relationships between the variation of match variables and football team’s match performance. Data from all 768 matches played at the group stage of UEFA Champions League from 2009-2010 to 2016-2017 seasons were analyzed. The correlations between the coefficient of variation of twenty match variables and the points of group stage were calculated. Autocorrelation function was used to identify the relationships between coefficients of variation of variables. Moreover, a generalized linear model was employed to identify the linear relationships between coefficients of variation and the probability of qualifying to the knockout stage. Inferences were made using the non-clinical magnitude-based inferences and evaluated by the smallest worthwhile change. Results showed that qualified teams showed more stable match performance on variables related to goal scoring, attacking and passing, while non-qualified teams displayed more stable match performance on variables related to defending. The coefficients of variation of variables related to goal scoring, attacking and passing had negative relationships with match performance, while variables related to defending displayed positive relationships. Findings of this study can provide useful information about the stability of match variables, contributing to the development of specific training interventions to enhance team’s performance in key indicators.